Analysis of the expectation dynamics and discourse on the metaverse using X(Twitter) data - Kyongchyol Yang; Jaemin Jung (International Telecommunications Society (ITS), 2024)
This study aims to empirically investigate the role of expectations in innovation diffusion using metaverse discourse on social media. We also explore the dominant discourses that emerged during significant periods when expectations shifted. Expectations play a crucial role in the hype cycle and are involved in determining the direction of technological change and the speed of adopting innovations. We analyzed tweet data containing metaverse from January 2021, the year the metaverse first gained public attention, to May 2023, the latest available date. We performed topic modeling and extracted 218 topics. Results revealed that the peak number of tweets in the metaverse was concentrated in specific periods, but the timing of the decline in the number of tweets shows different patterns depending on the topic. After categorizing the extracted topics into themes, we conducted sentiment analysis to observe expectation changes. Expectations of metaverse technology changed over time: initially, positive emotional expectations were high, but after a certain point, they declined. From the discourse analysis, we found that the Metaverse was initially hyped and faced technical and practical limitations. The decline in expectations reflects these limitations. The combination of topic modeling and sentiment analysis provides a new approach to investigating public discourse and a comprehensive view of the collective flow around new technologies.
Keywords: 330; Metaverse; Innovation diffusion; Innovation expectation; Hype cycle